2019
DOI: 10.1002/aenm.201902675
|View full text |Cite
|
Sign up to set email alerts
|

Operando Observations of SEI Film Evolution by Mass‐Sensitive Scanning Transmission Electron Microscopy

Abstract: SEI films directly affect the dissolution and deposition of lithium during discharge and charge and thus are one of the key factors that determine the safety, power capability, morphology of lithium deposits, shelf life, and cycle life of LIBs. In particular, the breakdown of SEI can result in the nucleation and growth of lithium dendrites and cause the safety risk for the practical applications of LIBs in the electric vehicles and other high-energy-density electronic devices. [5,6] While, a stable and robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…[ 7 ] It has been observed by operando scanning transmission electron microscopy that the SEI layer is damaged during interfacial fluctuations and finally exfoliated, leaving an exposed electrode surface in the electrolyte. [ 8 ] The SEI layer exfoliation can be attributed to poor chemical adhesion between the SEI layer and the Li substrate. Obviously, a stable and robust SEI layer is the decisive factor for safe, dendrite‐free, and long‐lifespan Li metal based batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] It has been observed by operando scanning transmission electron microscopy that the SEI layer is damaged during interfacial fluctuations and finally exfoliated, leaving an exposed electrode surface in the electrolyte. [ 8 ] The SEI layer exfoliation can be attributed to poor chemical adhesion between the SEI layer and the Li substrate. Obviously, a stable and robust SEI layer is the decisive factor for safe, dendrite‐free, and long‐lifespan Li metal based batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 80 ] The causes for the preferential distribution of these organic/inorganic species are related to the initial decomposition sequence of electrolyte ingredients [ 82 ] and the subsequent evolution process of initial SEI. [ 83 ] The originally generated organic species might get further reduced to form more stable inorganic components near the surface of electrode, which play an essential role in achieving the electronic insulation of SEI. [ 84 ] Further, Cheng et al indicated that the layered model and mosaic model are not contradictory in essence, since the building blocks in each layer of layered model still distribute in a mosaic form.…”
Section: Structure and Component Models Of Seimentioning
confidence: 99%
“…e) The configuration of lithium ion microcell with three electrodes for electrochemical measurements Schematic picture of the closed cell and testing mechanism and the in situ HAADF‐STEM images of Au lithiation. [ 23 ] Reproduced with permission. [ 23 ] Copyright 2019, Wiley‐VCH.…”
Section: Electron Microscopy Imaging Techniquementioning
confidence: 99%
“…Therefore, this technique was able to visualize the nanoscale chemical valence change, and reveal the lithiation mechanism. Similar in situ TEM cells were also used to study the lithiation process of Li‐alloying process, [ 22 ] SEI evolution, [ 23 ] and lithium dendrite growth. [ 24 ]…”
Section: Electron Microscopy Imaging Techniquementioning
confidence: 99%